Prevention of mother to child transmission of Human Immunodeficiency virus (HIV): What do Ghanaian Midwives know? - Dora Ganyo Donkor; Vivian Efua Senoo-Dogbey (International Journal of Africa Nursing Sciences, 2023)
Background: Prevention of Mother to Child Transmission (PMTCT) is an important public health intervention that has significantly reduced the risk of mother-to-child transmission of Human Immunodeficiency Virus (HIV) from 40% to close to 5%. Midwives need to have good knowledge of this important preventive strategy to be able to contribute to global efforts aimed at the elimination childhood HIV infections and all other forms of HIV infection. Methods: This research employed an analytical cross-sectional study design and recruited 179 Midwives through purposive sampling. A self-administered questionnaire was completed by participants to test their knowledge regarding PMTCT for HIV. Analysis of data was done through STATA using ANOVA, binary logistic regression analysis with a level of significance set at < 0.05. Findings: The knowledge levels observed in this study include High (48%), moderate (35.2%), and Low (16.8%) with an overall mean score of 67.82 indicating a moderate level of knowledge among the studied sample. Having a master’s degree (aOR = 1.3; 95 % CI = 0.1–0.9). and age (aOR = 14.9; 95 % CI = 0.6–0.9) were factors that showed statistically significant association with having good knowledge of the guidelines. Conclusions: Even though most of the participants were within the level of high knowledge of the guidelines, overall knowledge at among the studied sample was level moderate. Knowledge improved with increasing age. Midwives with master’s degree demonstrated good knowledge of the guidelines. Support in the form of training is needed to achieve optimum knowledge of the PMTCT guidelines among midwives who are the main implementers of the PMTCT strategy in Ghana.